Conducting poly(ether imide)-graphite composite for some solvent vapors sensing application - Cakar, Fatih; Moroglu, M. Reyhan; Cankurtaran, Husnu; Karaman, Ferdane (ELSEVIER SCIENCE SA, 2010)
The electrical resistance responses of a sensor based on graphite loaded poly(ether imide) (Ultem (R) 1000) were measured upon exposure to various organic solvents. It was found that the responses of the composite to the solvents are drastically consistent with their relative energy difference (RED) values obtained from Hansen partial solubility parameters. The specific retention volumes of some alkanes, aromatics and aliphatic esters similar to sensed solvents were obtained on the sensor composite in the column of a gas chromatography. It was seen that the responses of the composite to the solvent vapors vary almost linearly with the logarithm of the specific retention volumes of the corresponding solvents. The weight fraction activity coefficients at infinite dilution of the solvents were also determined at temperatures between 260 and 285 degrees C. It was seen that Ultem (R) 1000/graphite composite film can be used as a sensor element to detect chloroform and chlorobenzene. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Vapor sensor; Poly(ether imide)-graphite composite; Polymer-solvent interactions; Hansen solubility parameters; Relative energy difference; Partial molar enthalpy changes; GAS-CHROMATOGRAPHY; CARBON NANOTUBES; POLYMER; SENSOR; ARRAYS; NANOCOMPOSITE; SENSITIVITY; PARAMETERS; GRAPHITE; Chemistry; Electrochemistry; Instruments & Instrumentation